2013
DOI: 10.1177/0020764013502469
|View full text |Cite
|
Sign up to set email alerts
|

The interrelationships between moral attitudes, posttraumatic stress disorder symptoms and mixed lateral preference in Israeli reserve combat troops

Abstract: Our findings suggest that moral objection has significant implications on combatant's psychological and organic well-being. The findings highlight the need to include moral attitudes in research and clinical practice among combat personnel and veterans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Moreover, 31% of the veterans experienced at least one of the MI betrayal events. These rates are similar to other reports around the world (Hoge et al., ; Jordan et al., ) and in Israel (Ritov & Barnetz, ). However, this is the first study that examined a broad range of PMIEs and thus allowed us to capture the oversized dimension of this experience over time.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, 31% of the veterans experienced at least one of the MI betrayal events. These rates are similar to other reports around the world (Hoge et al., ; Jordan et al., ) and in Israel (Ritov & Barnetz, ). However, this is the first study that examined a broad range of PMIEs and thus allowed us to capture the oversized dimension of this experience over time.…”
Section: Discussionsupporting
confidence: 92%
“…Among Israeli veterans, one study found that as compared to veterans who have not been exposed to or degraded Palestinian civilians reported more PTSS and higher rates of PTSD (Bleich et al., ). The second study among reserve combat troops revealed that veterans with high moral objection reported significantly more PTSS in comparison to participants with low moral objection (Ritov & Barnetz, ). To the best of our knowledge, there are no studies that directly examined the wide spectrum of PMIEs and their associations with PTSS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Military service and particularly involvement in military occupation and urban war that includes civilians may lead to antiwar stances, moral objection, and peace activism (Sasson‐Levy, Levy, & Lomsky‐Feder, ). It is believed that moral objection in the military may affect the severity of PTSD symptoms among combatants (Ritov & Barnetz, ). However, in our study, similar to previous studies regarding the reality of security threats and intractable conflicts (Bar‐Tal ; Halperin, Bar‐Tal, Sharvit, Rosler, & Raviv, ; Kriesberg ), the combatants focused mainly on the traumas of their own “side” of the conflict and did not focus on moral objection.…”
Section: Discussionmentioning
confidence: 99%
“…By exploring the experiences of combatants in the military, we can learn more about gendered practices. The military environment causes soldiers—both men and women—to feel that they should repress their emotions (Ritov, & Barnetz, ), and this practice is considered to be “normal” in military institutional practice (Kronsell, ). Van der Kolk et al () claim that as long as memories of the trauma remain detached and dissociated, they might be expressed as psychiatric symptoms that will interfere with proper functioning in the future.…”
Section: Findings: Potentially Traumatic Events and Women Combatants mentioning
confidence: 99%